Luonto historiakuvan loimilangaksi? Luonnonympäristölle annetut merkitykset pohjoiskarjalaisessa matkailussa - Ilmolahti, Oona (Matkailututkimus, 2019)
Nature and culture are often seen as two separate entities in the travel industry. In this article, it is argued that nature is an essential part of human culture, and nature tourism should also be interpreted through cultural concepts. Cultural nature is addressed by examining the historical imaginaries used in the tourist attractions within the North Karelia Biosphere Reserve in Eastern Finland. The main scope of interest is how nature is implicated in the local narratives of the past, and how history and nature are intertwined in nature attractions such as national parks. The findings will be viewed with the help of a museological significance assessment, which enables the examination of the different meanings given to cultural nature in tourism. The cultural information about local nature and human traces of human life in nature can be regarded as enhancing the attractiveness of the area and as constituting an integral part of the nature experience. National parks can be seen as nature museums, which originally sought to preserve samples of virginal forests, thus representing the nature relationship of the previous generations. Nature, the key attraction of the area, is deeply connected with the local history culture and imaginaries of the exotic wilderness of Karelianism. The national romantic view bypasses to some extent the local experience and stories by emphasising the 19th-century national romantic artists and images related to historical Border Karelia.